Improved BM Pattern Matching Algorithm for Intrusion Detection - Qingzhang Chen; Yibo Niu; Zhehu Wang; Feng Du (2010 Third International Joint Conference on Computational Sciences and Optimization, 2010)
In the paper, two improved algorithms: BMLT and BMLS are proposed, in which the time complexity and space complexity of BM is improved. The algorithm of BMLT with a new pre-calculation function can increase in the movement of pattern significantly. The algorithm of BMLS can reduce the space complexity and maintain the time complexity by reducing a pretreatment function and recording the number of times that a bad char found in the pattern. Experiments indicate that the time complexity is reduced by 60% and the space complexity is reduced by 26% at most. Therefore, the improved algorithms can provide significant improvement in pattern matching performance when using in an IDS.